Hydrodynamical interaction of stellar and planetary winds: effects of charge exchange and radiation pressure on the observed Ly α absorption. Issue 4 (28th June 2019) - Esquivel, A; Schneiter, M; Villarreal D'Angelo, C; Sgró, M A; Krapp, L
ABSTRACT: Lyman α observations of the transiting exoplanet HD 209458b enable the study of exoplanet exospheres exposed to stellar extreme ultraviolet (EUV) fluxes, as well as the interacting stellar wind properties. In this study we present 3D hydrodynamical models for the stellar–planetary wind interaction including radiation pressure and charge exchange, together with photoionization, recombination, and collisional ionization processes. Our models explore the contribution of the radiation pressure and charge exchange to the Ly α absorption profile in a hydrodynamical framework, and for a single set of stellar wind parameters appropriate for HD 209458. We find that most of the absorption is produced by the material from the planet, with a secondary contribution of neutralized stellar ions by charge exchange. At the same time, the hydrodynamic shock heats up the planetary material, resulting in a broad thermal profile. Meanwhile, the radiation pressure yields a small velocity shift of the absorbing material. While neither charge exchange nor radiation pressure provides enough neutrals at the velocity needed to explain the observations at −100 km s −1 individually, we find that the two effects combined with the broad thermal profile are able to explain the observations.